Control de bienes larga duración en la Casa de la Cultura Ecuatoriana Núcleo de Los Ríos - Quiñonez Leon, Evelin Stefania (2021)
The present case study was carried out in order to analyze and learn about the control of long-term assets within the public financing institution Casa de la Cultura Nucleo de Los Ríos, which belongs to the Ministry of Culture. On many occasions, the management, control and correct use of long-term administrative assets in the public sector has been a problem for them over time, and with this it has triggered the poor organization of their resources despite the existence of of manuals and systems that help keep track of them. To obtain the information, it was necessary to use methodologies such as descriptive research since observed situations are narrated and described, the direct observation technique and the interview with the Analyst responsible for the goods were used to collect the information.